A re-look at canal irrigation system performance: a pilot study of the Sina Irrigation System in Maharashtra, India - Amarasinghe, Upali A.; Sikka, Alok; Mandave, Vidya; Panda, R. K.; Gorantiwar, S.; Chandrasekharan, Kiran M.; Ambast, S. K. (IWA Publishing, 2021)
The general perception of canal irrigation systems in India is one of built infrastructure with low service performance. This paper presents an analytical framework, applied to the Sina medium irrigation system in Maharashtra state of India, to study the performance of an expanded water influence zone (WIZ) including a buffer zone outside the canal command area (CCA) influenced by the irrigation system’s water resources. The framework used satellite-based estimates of land-use and cropping patterns. The results indicate that there is hardly any gap between the irrigation potential created (IPC) and the irrigation potential utilized (IPU) in the CCA. The fraction of consumptive water use (CWU) of irrigation is low in the CCA, but almost one in the WIZ, due to the reuse of return flows in the WIZ. Future investments should focus on increasing economic water productivity ($/m3 ) in order to enhance the resilience of the farming community in the WIZ, which is frequently affected by water scarcity.